Dampak Implementasi Program Merdeka Belajar Kampus Merdeka (MB-KM) Terhadap Mahasiswa Program Studi Teknologi Pangan - Amelia, Julfi Restu; Romadhan, M Fajri (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Food Technology Department, Sahid University - Jakarta, has implemented the Merdeka Belajar Kampus Merdeka (MB-KM) program, so it is necessary to measure the impact of the implementation  on student. This research aims 1) to know the impact of implementing MB-KM on student of  Food Technology Department, Sahid University - Jakarta, and 2) to explain the implementation of the MB-KM program to build the entrepreneurial spirit of students in the form of SAFOTECH EXPO activities. The research stages are research preparation, data collection and literature study, and data processing-discussion. The results showed that 96.2% of students stated that all MB-KM activities were relevant to the program in Food Technology Department. The results also showed that one of the most popular activities for students in the MB-KM program is entrepreneurial activity, 3) SAFOTECH EXPO is a form of implementing the MB-KM program which is in line with the learning activity program contained in the study program to support student interest in conducting entrepreneurial activities.